No solution because you can’t even out both sides
Answer:
-13a^2 + 170ab - 13b^2.
Step-by-step explanation:
1. 36(a+b)^2 - 49(a-b)^2
This is the difference of 2 squares: a^2 - b^2 = (a + b)(a - b).
36(a+b)^2 - 49(a-b)^2
= (6(a + b) + 7(a - b))( 6(a + b) - 7(a - b))
= (6a + 7a + 6b - 7b)( 6a - 7a + 6b + 7b)
= (13a - b)(-a + 13b)
If you require the expansion of this it is:
-13a^2 + 170ab - 13b^2.
The total time taken to cover 12 miles distance is 5 hours.
<u>Given the Parameters</u> :
- Total distance hiked = 12 miles
Recall :
Let :
<u>We could create an equation thus</u> :
Total distance = 3(2) + 2(t - 2)
12 = 6 + 2t - 4
12 = 2 + 2t
12 - 2 = 2t
10 = 2t
t = 10/2
t = 5
Therefore, the total time taken is 5 hours
Learn more :brainly.com/question/18796573